Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

We have a function: $\phi : U \to \mathbb{R}^l$, where $U \subseteq \mathbb{R}^k$ is an open subset. $\phi$ is a function of class $C^1$, differentiable in $q$, $q \in U$. Let $\displaystyle q_n \to q$ and $\displaystyle \phi(q_n) \to \phi(q)$ while $\displaystyle n \to \infty$. How to prove that: $$ \lim_{n \to \infty} \frac{D\phi (q) (q_n - q)}{||q_n -q||} = \lim_{n \to \infty} \frac{\phi (q_n) - \phi(q)}{||q_n -q||} \text{?} $$ There is a hint to use the definition of $D\phi(q)$ and a fact that it is a linear map. I tried to write it using the definition, but it didn't work. Please, help me.

share|improve this question
add comment

1 Answer

It is not true in general.

Let $\phi(x) = x$, and choose $q=0$, and $q_n = (-1)^n\frac{1}{n}$. Then $\frac{q_n-q}{\|q_n-q\|} = (-1)^n$, and hence $\frac{D\phi(q)(q_n-q)}{\|q_n-q\|} = (-1)^n$, which has no limit as $n \to \infty$.

What is true, however, is that $\lim_n (\frac{\phi(q_n)-\phi(q)}{\|q_n-q\|} - \frac{D\phi(q)(q_n-q)}{\|q_n-q\|}) = 0$.

To see this:

By definition of $D\phi(q)$, you have for all $\epsilon>0$, there exists a $\delta>0$ such that if $\|q'-q\|< \delta$, then $\|\phi(q')-\phi(q) - D\phi(q)(q'-q)\| \leq \epsilon \|q'-q\|$.

Let $\epsilon >0$, then for $n$ sufficiently large we have $\|q_n-q\| < \delta$, and so $\|\phi(q_n)-\phi(q) - D\phi(q)(q_n-q)\| \leq \epsilon \|q_n-q\|$.

If we assume that $q_n \neq q$ for all $n$ sufficiently large, we can divide across to get $\|\frac{\phi(q_n)-\phi(q)}{\|q_n-q\|} - \frac{D\phi(q)(q_n-q)}{\|q_n-q\|}\| \leq \epsilon$, from which it follows that $\lim_n (\frac{\phi(q_n)-\phi(q)}{\|q_n-q\|} - \frac{D\phi(q)(q_n-q)}{\|q_n-q\|}) = 0$.

share|improve this answer
    
But I thought about such explanation: $\lim_{n \to \infty} \frac{D \phi(q)(q_n -q)}{||q_n -q||} = \lim_{n \to \infty} \frac{\phi(q+q_n-q)-\phi(q) - r(||q_n -q||)}{||q_n-q||} = \lim_{n \to \infty} \frac{\phi(q_n) - \phi(q)}{||q_n-q||} - \frac{r(||q_n-q||)}{||q_n-q||}$ and so we get our equation since, by definition, $\lim_{n \to \infty} \frac{r(||q_n-q||)}{||q_n-q||} =0$. So isn't it ok? Why? –  Anne Jan 27 '13 at 15:27
    
Oh, and if we know that $\lim_{n \to \infty} \frac{D\phi(q)(q_n-q)}{||q_n-q||}$ has a limit- is it true then? –  Anne Jan 27 '13 at 15:33
    
Yes, since if $a_n-b_n$ has a limit and $b_n$ has a limit, then $a_n = (a_n-b_n)+b_n$ has a limit. –  copper.hat Jan 27 '13 at 17:18
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.